Eternal Perspective: Christian Leadership as an Antidote to Greed and Organizational Deviance - Hoga Saragih; Tan Lie Lie; Janto Chandra (Journal of Educational, Health and Community Psychology, 2026)
This study explores how Christian church leaders construct and enact an eternal perspective within organizational leadership practices. Using a Heideggerian phenomenological design, data were collected through semi-structured interviews with five church leaders who had served in leadership roles for at least five years. Data were analyzed using reflexive thematic analysis. Four major themes were generated: integrity as the integration of faith and organizational governance, servant leadership as resistance to power-centered leadership, spiritual accountability and stewardship as moral safeguards, and eternal perspective as resistance to greed and organizational deviance. The findings show that eternal perspective functions not merely as a theological belief but as a practical moral-spiritual framework that shapes ethical decision-making, transparent governance, long-term vision, and resistance to misuse of authority and resources. This study contributes to spiritual and servant leadership literature by positioning eternal perspective as a moral-regulatory mechanism that strengthens integrity, stewardship, and ethical accountability in faith-based organizations.